2017
DOI: 10.1158/1535-7163.mct-17-0171
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Targets of Combined mTOR/HDAC Inhibition Promote MYC Degradation

Abstract: Cancer treatments often require combinations of molecularly targeted agents to be effective. mTORi (rapamycin) and HDACi (MS-275/entinostat) inhibitors have been shown to be effective in limiting tumor growth, and here we define part of the cooperative action of this drug combination. More than 60 human cancer cell lines responded synergistically (CI<1) when treated with this drug combination compared to single agents. In addition, a breast cancer patient-derived xenograft, and a BCL-XL plasmacytoma mouse mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…1a, b , and Supplementary Table 1 ) 31 , 32 . Most compounds were evaluated for affinity and effects on cell viability, and selected compounds also for effects on MYC protein levels in L363 cells (a MYC-driven multiple myeloma cell line 33 ). Affinities were generated by measuring K D values determined by the compound-induced change in fluorescence of an Alexa Fluor® 647 tag conjugated to the 5′ end of Pu27.…”
Section: Resultsmentioning
confidence: 99%
“…1a, b , and Supplementary Table 1 ) 31 , 32 . Most compounds were evaluated for affinity and effects on cell viability, and selected compounds also for effects on MYC protein levels in L363 cells (a MYC-driven multiple myeloma cell line 33 ). Affinities were generated by measuring K D values determined by the compound-induced change in fluorescence of an Alexa Fluor® 647 tag conjugated to the 5′ end of Pu27.…”
Section: Resultsmentioning
confidence: 99%
“…Simmons and his colleagues demonstrated synergistic interactions between rapamycin and entinostat (small molecule inhibitor of Class 1 HDAC) in B cells neoplasia, in both in vitro and in vivo models ( Table 2 ) [ 83 ]. Subsequently, the same group demonstrated that this combination is synergistic in other cancer cell lines with different histological origin (i.e., BC and plasmacytoma) and hypothesized that Myc could be a central player in this combination strategy [ 106 ]. Combination approaches include different epigenetic drugs, such as azacitidine, a chemical analog of cytidine which inhibits DNA methyltransferase, causing hypomethylation of DNA; a phase Ib/II study to assess the effects of everolimus in combination with azacitidine in AML patients has been reported [ 107 ].…”
Section: Mtorc1 and Mtorc2 And Their Cross-talk With Other Pathwaymentioning
confidence: 99%
“…In this study, we found that, similar to genetic depletion of Snail, pharmacological inhibition of HDAC activity significantly repressed Snail activity by inducing 4E-BP1 expression, and co-targeting HDAC and mTOR resulted in a marked suppression of tumor growth. Several recent studies 55 57 also show that the combination of mTOR and HDAC inhibitors exert a synergistic antitumor activity in a large panel of human cancer cell lines, and the patient-derived xenograft and transgenic mouse models. Interestingly, the synergistic growth inhibiting consequence of combined mTOR/HDAC inhibition is likely attributed to their mechanistic convergences on the mTOR/4E-BP1 signaling axis and impaired polysome formation 56 .…”
Section: Discussionmentioning
confidence: 95%